Sigma-lead Male-to-Female Gender Affirmation Surgery: Blending Cosmesis with Functionality - Kaushik, Narendra (Plast Reconstr Surg Glob Open, 2019)
BACKGROUND: Current male-to-female (MtF) sex-reassignment-surgery techniques have not been fully successful to achieve the ideal objectives. The ordeal of multiple procedures, associated complications, and suboptimal results leads to high rate of dissatisfaction. We have tried to overcome functional inadequacy and address the esthetic issues for outer genitalia and vagina with our innovative “true shape sigma-lead SRS: Kaushik’s technique,” which has now become the technique of choice for MtF genital SRS for our patients. METHODS: Between April 2007 and April 2017, authors performed 386 sigma-lead SRS in MtF transsexuals. Results were analyzed based on complications, resurgeries, and esthetic/functional outcomes. Corrective SRS using rectosigmoid constituted 145 cases and is not a part of this study. RESULTS: Maximum follow-up was 7 years (average 34 months). Seventy-eight (20.2%) patients had complications, majority being minor (97.4%). Forty-four (11.4%) required resurgeries, 10 (2.6%) were corrective for introital stricture and mucosal prolapse, whereas 34 (8.8%) opted for optional minor esthetic enhancement. The overall satisfaction rate for cosmetic and functional outcomes was 4.7 out of 5. In addition to review of the literature, innovations in the technique have been explained. CONCLUSIONS: Kaushik’s sigma-lead MtF SRS technique is a step short to become the gold standard of genital SRS because it has proven to be safe and reliable. It allows faster healing, minimal dilation, and nearly natural cosmetic results in the form of clitoris/clitoral hood, labia minora, labia majora along with self-lubricating, fully deep, and sensate neovagina with orgasmic capabilities. This is perhaps the largest reported series of rectosigmoid use in transsexuals carried out for primary vaginoplasty.